Scientific and statistical database management : 24th International Conference, SSDBM 2012, Chania, Crete, Greece, June 25-27, 2012. Proceedings - Bowers, Shawn; Ailamaki, Anastasia (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 24th International Conference on Scientific and Statistical Database Management, SSDBM 2012, held in Chania, Grete, Greece, in June 2012. The 25 long and 10 short papers presented together with 2 keynotes, 1 panel, and 13 demonstration and poster papers were carefully reviewed and selected from numerous submissions. The topics covered are uncertain and probabilistic data, parallel and distributed data management, graph processing, mining multidimensional data, provenance and workflows, processing scientific queries, and support for demanding applications.